Analisis Pengaruh Daya Tarik Iklan, Kualitas Pesan Iklan dan Frekuensi Penayangan Iklan Terhadap Efektivitas Iklan TV Tokopedia - Dasmansyah Adyas; Annisa Khairani (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2019)
This research is a causality study that aims to find out the influence of advertisement attractiveness, advertisement message quality, and viewing freuency as independent variable to the effectiveness of advertisement on television especially tokopedia advertisement, as the dependent variable. The methodology used in this study are multiple linear regression, classical assumption test, multicollinearity test, heteroscedastic test, t test, and f test. The results of the study showed that independent variables (the influence of advertisement attractiveness, advertisement message quality, viewing frequency) affect ( the dependent variable (advertisement effectiveness), both partially and simultaneously.